PENGARUH MEDIA PEMBELAJARAN DAN KECERDASAN LOGIS MATEMATIS TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Mujiani, Dwi Safitri (Pascasarjna Universitas Negeri Jakarta, 2016)
Abstract: The aim of this experimental study is determine the effect of teaching aid on math learning outcomes. This research was conducted in Elementary School on fifth grade, by using simple random sampling technique that has been done to 58 students. The data is collected by test and analyzed by using analysis variant (ANAVA) two way design with treatment by level 2x2. Based on the results and discussion, it concluded that (1) the mathematics learning outcomes of students who use models media are higher than students who use printing media, besides the use of models media give 90.1% effect on learning outcomes, (2) there is interaction effect between the application of teaching aid and mathematical logical intelligence towards learning outcomes of mathematics, (3) the mathematics learning outcomes of students taught by using models media are higher than students taught by using printing media on a group of students who have high mathematical logical intelligence and (4) the mathematics learning outcomes of students by using models media in low level of mathematical logical intelligence is not higher than the mathematics learning outcomes of students by using printing media in low level of mathematical logical intelligence. The results of this study indicates that models media with mathematical logical intelligence can improve mathematics learning outcomes of students.Keywords: models media, printing media, mathematical logical intelligence, mathematics learning outcomesAbstrak: Penelitian eksperimen ini bertujuan untuk mengetahui pengaruh media pembelajaran terhadap hasil belajar matematika. Penelitian ini dilaksanakan di Sekolah Dasar Siswa kelas V dengan menggunakan teknik simple random sampling yang telah dilakukan kepada 58 siswa. Pengambilan data diperoleh melalui tes dan dianalisis menggunakan analisis varian (ANAVA) dua jalan dengan desain Treatment by Level 2x2. Berdasarkan hasil dan pembahasan, diperoleh kesimpulan bahwa (1) hasil belajar matematika siswa yang menggunakan media model lebih tinggi dibandingkan dengan siswa yang menggunakan media cetak, selain itu penggunaan media model berpengaruh sebesar 90,1% terhadap hasil belajar, (2) terdapat pengaruh interaksi antara pemberian media pembelajaran dan kecerdasan logis matematis terhadap hasil belajar matematika siswa, (3) hasil belajar matematika antara siswa yang diajarkan menggunakan media pembelajaran model lebih tinggi dari siswa yang diajarkan menggunakan media pembelajaran cetak pada kelompok siswa yang memiliki kecerdasan logis matematis tinggi, dan (4) hasil belajar matematika menggunakan media pembelajaran model dengan tingkat kecerdasan logis matematis rendah tidak lebih tinggi dari hasil belajar matematika menggunakan media pembelajaran cetak dengan tingkat kecerdasan logis matematis rendah. Hasil penelitian ini menunjukkan bahwa media pembelajaran model dengan kecerdasan logis matematis mampu meningkatkan hasil belajar matematika siswa.Kata kunci: media pembelajaran, media model, media cetak, kecerdasan logis matematis, hasil belajar matematika